Wrongs known as right in thyroid scintigraphy and uptake study - Gül, Serdar Savaş (The European Research Journal, 2019)
Objectives: Thyroid scintigraphy using 99mTc-pertechnetate is commonly used to study function and structure of thyroid gland. Pin-hole collimator is generally preferred in thyroid scintigraphy and uptake studies. The purpose of the present study was to determine actual radiopharmaceutical uptake value in an experimental 99mTc-pertechnetate thyroid scintigraphy and uptake model. Methods: Thyroid hyperactive and hypoactive nodule models were created using 4 mCi (148 MBq) 99mTc-pertechnetate. In the experimental model, 4 mm, 6 mm and 8 mm diameter pin-hole collimators, and 5 cm, 7 cm and 10 cm object-to-pinhole distances were investigated. Results: In thyroid hyperactive nodule model, despite the same activity value, uptake at 7 cm object-to-pinhole distance was higher compared to 10 cm distance (122% and 103%, respectively). In the patient with Graves’ disease, despite the same activity value, uptake at 5 cm object-to-pinhole distance was higher compared to 10 cm distance (8% and 4%, respectively). In thyroid hypoactive nodule model, 4 mm, 6 mm and 8 mm diameters pin-hole collimators were imaged at 5 cm, 10 cm and 15 cm object-to-pinhole distances. The resolution differences between the images were evaluated. Conclusion: It was determined that imaging using 10 cm object-to-pinhole distanceand 4 mm diameter pin-hole collimator was best in terms of image resolution and optimum 99mTc-pertechnetate uptake level.